2015
DOI: 10.1097/mlr.0000000000000301
|View full text |Cite
|
Sign up to set email alerts
|

Infertility Care Among OEF/OIF/OND Women Veterans in the Department of Veterans Affairs

Abstract: Background An increasing number of young women Veterans seek reproductive health care through the VA, yet little is known regarding the provision of infertility care for this population. The VA provides a range of infertility services for Veterans including artificial insemination, but does not provide in vitro fertilization. This study will be the first to characterize infertility care among OEF/OIF/OND women Veterans using VA care. Methods We analyzed data from the OEF/OIF/OND roster file from the Defense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 19 publications
(22 reference statements)
0
30
0
Order By: Relevance
“…The limited studies of infertility in U.S. Veterans suggest a prevalence of the disease in Veterans Affairs (VA)-enrolled Veterans that is similar to the general U.S. populations when self-report is used (13.8% in male Veterans and 15.8-19% in female Veterans). 16,17 In contrast, medical record review reveals very low rates of infertility diagnosis in female Veterans (1.9%), 18,19 suggestive of the under identification by health care providers and unawareness and underutilization of VHA infertility care options by both patients and health care providers.…”
Section: Estimates Of Veteran Infertility and Available Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The limited studies of infertility in U.S. Veterans suggest a prevalence of the disease in Veterans Affairs (VA)-enrolled Veterans that is similar to the general U.S. populations when self-report is used (13.8% in male Veterans and 15.8-19% in female Veterans). 16,17 In contrast, medical record review reveals very low rates of infertility diagnosis in female Veterans (1.9%), 18,19 suggestive of the under identification by health care providers and unawareness and underutilization of VHA infertility care options by both patients and health care providers.…”
Section: Estimates Of Veteran Infertility and Available Researchmentioning
confidence: 99%
“…21 While direct injury to the urogenital region is a clear cause of infertility, research suggests there are other, less pathologically straightforward service-related causes of infertility. For example, studies have shown associations in Veterans between infertility and sexual assault [17][18][19] and posttraumatic stress disorder 17,18 as well as between infertility and other mental health disorders such as depression. 18,19 VHA Policies on Infertility Coverage…”
Section: Estimates Of Veteran Infertility and Available Researchmentioning
confidence: 99%
“…Two large studies utilizing US Department of Defense and Veterans Affairs' (VA) data examined infertility among US servicewomen (Katon et al, 2014;Mattocks et al, 2015). Rivera and Johnson identified that US female veterans of Vietnam and the first Gulf War reported more reproductive and gynaecological problems than the general population (Rivera and Johnson, 2014).…”
Section: Articlementioning
confidence: 99%
“…Only three manuscripts examined infertility among Veterans (Supplementary Table 3). [41][42][43] None used standard measures of infertility (time to pregnancy). 44 Self-reported lifetime sexual assault was positively associated with involuntary childlessness (aOR, 2.02; 95% CI, 1.39-2.95).…”
Section: Infertilitymentioning
confidence: 99%
“…43 Among Veterans who served during the Afghanistan and Iraq conflict era, women Veterans were more likely to report a lifetime history of infertility relative to their male counterparts (aOR, 1.17; 95% CI, 1.04-1.31), 42 and among those using VA healthcare who had an infertility diagnosis, those who were obese were more likely to receive an infertility assessment or treatment (37.6 vs. 28.5%). 41 Pregnancy.…”
Section: Infertilitymentioning
confidence: 99%